Constructing Z-scheme based CoWO4/CdS photocatalysts with enhanced dye degradation and H2 generation performance. (27th September 2018) - Cui, Haojie; Li, Beibei; Zhang, Yuzhe; Zheng, Xudong; Li, Xiazhang; Li, Zhongyu; Xu, Song
Abstract: The artificial Z-scheme photocatalysts, simulating the natural photosynthesis, enables more efficient utilization of solar energy for sustainable fuel production. A novel direct Z-scheme CoWO4 /CdS binary photocatalyst is synthesized by an in-situ hydrothermal method, and the enhanced activities of H2 production and dye degradation are attained. The rate of H2 production is 15.91 mmol/h/g, which is 24-fold higher than CdS. The CoWO4 /CdS composites exhibited outstanding stability after five consecutive reactions. Meanwhile, the photocatalytic removal efficiencies of MG are about CdS < CWC-0.8 < CWC-1.0 < CWC-1.4 < CWC-1.2. The preeminent photocatalytic property of CoWO4 /CdS composites is authenticated based on Z-scheme heterojunction. Most importantly, the enhancement mechanism is attributed to the effective isolation of photogenerated carriers and the existance of redox capabilities for CoWO4 /CdS system. This work might provide novel conception for the design and construction of high-performance photocatalysts with direct Z-scheme. Graphical abstract: Highlights: New CoWO4 /CdS composites were fabricated by in-situ hydrothermal method. The composites were active for H2 evolution and dye degradation under visible light. The apparent quantum efficiency of the composites was as high as ca. 51%. Z-scheme charge carrier transfer was proved by radical scavenging experiment and XPS.